The role of Convalescent Plasma in modulating the inflammatory response in COVID-19 patients (Research, Society and Development, 2024)
Introduction: The COVID-19 pandemic has had a devastating impact on global public health, causing over 6.9 million deaths. Many therapeutic strategies were used in an attempt to find a cure and prevent complications from this infection. Among these was convalescent plasma therapy, which involves the transfusion of plasma from individuals who have recovered from the infection, containing specific antibodies against the pathogen. Objective: To evaluate the effectiveness of convalescent plasma therapy in improving the clinical condition of hospitalized COVID-19 patients and its relationship with plasma levels of anti-SARS-CoV-2 antibodies. Methodology: A bibliographic search was conducted on the PubMed and Virtual Health Library platforms, and through inclusion and exclusion criteria, 20 articles were selected to support this systematic literature review. Results: This study showed that among the 20 articles included, 11 reported positive results regarding the use of convalescent plasma in modulating the inflammatory response of patients infected with the SARS-CoV-2 virus. Although this therapy did not present adverse effects, it did not affect the incidence of long-term symptoms, did not reduce mortality, and led to an increase in anti-SARS-CoV-2 antibody levels that was insufficient to alter the course of the disease in question. Conclusion: Although the administration of convalescent plasma is free of adverse effects, its effectiveness remains uncertain, and its use as a monotherapy is not recommended. Therefore, more research is needed to establish its applicability and true effectiveness.